2015
DOI: 10.1270/jsbbs.65.388
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for rice blast resistance detected in a local rice breeding population by genome-wide association mapping

Abstract: Plant breeding programs aim to develop cultivars with high adaptability to the specific conditions in a local region. As a result, unique genes and gene combinations have been accumulated in local elite breeding populations during the long history of plant breeding. Genetic analyses on such genes and combinations may be useful for developing new cultivars with more-desirable agronomic traits. Here, we attempted to detect quantitative trait loci (QTL) for rice blast resistance (BR) using a local breeding rice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Previously, we identified the blast resistant gene Pi-cd on chromosome 11 as a major genetic factor in the local rice population in Hokkaido (Fig. 3F), although it may be derived from a rice variety Cody from USA (Shinada et al 2015b). The Pi-cd locus is distributed specifically in tropical japonica (upland) rice varieties over the world and might be introgressed from wild relative O. meridionalis (Fujino et al 2019c).…”
Section: Premium Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we identified the blast resistant gene Pi-cd on chromosome 11 as a major genetic factor in the local rice population in Hokkaido (Fig. 3F), although it may be derived from a rice variety Cody from USA (Shinada et al 2015b). The Pi-cd locus is distributed specifically in tropical japonica (upland) rice varieties over the world and might be introgressed from wild relative O. meridionalis (Fujino et al 2019c).…”
Section: Premium Traitsmentioning
confidence: 99%
“…The rice variety Kitakurin was registered in 2014 and exhibits good eating quality and vigorous resistance to rice blast (http://www.pref.hokkaido.lg.jp/ns/nsk/kome/index3.htm). Pi-cd plays a major role in blast resistance in Kitakurin (Fujino et al 2019c, Shinada et al 2015b.…”
Section: Premium Traitsmentioning
confidence: 99%
“…Previously, we identified a blast resistance gene, Pi‐cd , on chromosome 11 as a major genetic factor in the local population in Hokkaido, Japan (Shinada et al., 2015). Hokkaido is the northernmost region of Japan and one of the northern limits of rice cultivation in the world (Fujino, Hirayama, & Kaji, 2019; Fujino, Obara, & Ikegaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hokkaido is the northernmost region of Japan and one of the northern limits of rice cultivation in the world (Fujino, Hirayama, & Kaji, 2019; Fujino, Obara, & Ikegaya, 2019). According to the pedigree of the varieties, Pi‐cd was transferred into the local population from the rice variety 'Cody' from America via the variety 'Kitaake', which was registered in 1984 (Shinada et al., 2015). Furthermore, characterization of the genome sequence around the Pi‐cd locus demonstrated that Pi‐cd may have originated from Oryza meridionalis (Fujino, Hirayama, Obara, & Ikegaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation